PROTOTIPE KULIAH UMUM BERBASIS UBIQUITOUS LEARNING PADA PENDIDIKAN JARAK JAUH - Tri Darmayanti (LPPM Universitas Terbuka, 2014)
The role of a highly credible academic lecturers or charismatic figures at a public lecture in a university are expected to affect behavior changes of the freshmen in understanding the core of the courses.. However, the public lecture has many obstacles if it would be implemented in distance education, because they are the limited number of charismatic figures, and the time constraints of the charismatic figures. With the development of information and communication technology (ICT), the public lecture presentation can be conducted through the use of ICT. In this way, the number of the target recipients become very large and can be spreaded out in many areas at once than if occurs in the face to face meetings. This study aims to: (1) develop a learning media prototype of a lecture-based ubiquitous learning (u-learning) or multi studio-based learning. The media is expected to show enlightenment from the charismatic figures that allow asynchronous learning, (2) empirically evaluate the validity and effectiveness of the use of the substance based learning media model u-learning. In accordance with the purpose of the study, the results of this research produce: (1) a learning media prototype containing lecture-based u-learning; (2) quantitative results of testing on the new student orientation activities (Orientasi Studi Mahasiswa Baru = OSMB) in the distance education regional office in Bandung (UPBJJ Bandung) which shows that all students responded positively. About the quality of media performance, 71.13% of the students commened good, while the students who answered good for the layout of the media are 68.25%, and the students who answered good for the systematics of public lectures are 70.38%, (3) results of qualitative data showed that the public lecture media is useful and accepted by the new students but not by the students of the last semester. In addition, the availability of electrical appliances and other technical equipment it should be considered if we would like to use this kind of media in remote areas. The prototype media or product generated from this study is expected to be used by various higher education institutions that require the content of the product, and can become an example for the development of a variety of enlightenment lecture materials. Peran tokoh akademisi berkredibilitas tinggi atau berkarisma dalam memberi pencerahan akademis pada suatu kuliah umum di perguruan tinggi diharapkan dapat mempengaruhi perubahan perilaku mahasiswa baru untuk memahami inti perkuliahan. Namun demikian, kuliah umum mengalami banyak kendala jika dilakukan pada pendidikan jarak jauh , karena keterbatasan jumlah tokoh keteladanan, dan keterbatasan waktu dari tokoh tersebut.Dengan perkembangan teknologi informasi dan komunikasi (TIK), kuliah umum dapat dilakukan melalui pemanfaatan TIK. Melalui cara ini, maka jumlah penerima materi atau sasaran target menjadi sangat besar dan dapat dilakukan di berbagai daerah sekaligus dibandingkan jika dengan pertemuan tatap muka. Penelitian ini bertujuan untuk: (1) mengembangkan prototipe media pembelajaran untuk kuliah umum berbasis ubiquitous learning (u-learning) atau multi studio-based learning. Media tersebut diharapkan dapat menampilkan pencerahan dari para tokoh yang memungkinkan terjadinya asynchronous learning; (2) melakukan evaluasi secara empirik validitas substansi dan efektivitas pemanfaatan model media pembelajaran berbasis u-learning. Sesuai dengan tujuan penelitian, maka hasil penelitian ini adalah (1) prototipe media media pembelajaran berisi kuliah umum berbasis u-learning, (2) secara kuantitatif, hasil uji coba pada kegiatan orientasi belajar mahasiswa baru (OSMB) di UPBJJ Bandung menunjukkan semua respon mahasiswa menanggapi secara positif. Untuk kualitas tampilan media, 71,13% mahasiswa menjawab bagus; sedangkan mahasiswa yang menjawab bagus sebesar 68,25% untuk tata letak media; dan mahasiswa menjawab sistematika materi kuliah umum termasuk bagus sebesar 70,38%; (3) secara kualitatif, hasil uji coba menunjukkan bahwa media kuliah umum ini bermanfaat dan dapat diterima oleh mahasiswa baru tetapi tidak oleh mahasiswa semester akhir. Pemanfaatan media di daerah terpencil juga perlu memperhatikan tentang ketersediaan peralatan listrik dan peralatan teknis lainnya. Prototipe media atau produk yang dihasilkan pada penelitian ini diharapkan akan dapat digunakan oleh berbagai instansi pendidikan tinggi yang membutuhkan, dan dapat dijadikan prototipe/contoh untuk pengembangan berbagai materi pencerahan lainnya.